2015
DOI: 10.4103/0971-5916.176564
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of dengue virus serotype 2 strains in the 2013 outbreak in Nepal

Abstract: Background & objectives:Epidemiological interventions and mosquito control are the available measures for dengue control. The former approach uses serotype and genetic information on the circulating virus strains. Dengue has been frequently reported from Nepal, but this information is mostly lacking. The present study was done to generate a comprehensive clinical and virological picture of a dengue outbreak in Nepal during 2013.Methods:A hospital-based study involving patients from five districts of Nepal was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
(19 reference statements)
2
17
0
Order By: Relevance
“…The study for 11 years with regards to the gender based analysis showed that the male population was more likely to have infection than female at the mean ratio of 2:1, which is in agreement to the past study done by Gupta et al [ 25 ]. One can assume that compared to women who are generally confined within household works the male population is mostly involved in outdoor work activities for livelihood which makes them more likely exposed to Aedes spp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study for 11 years with regards to the gender based analysis showed that the male population was more likely to have infection than female at the mean ratio of 2:1, which is in agreement to the past study done by Gupta et al [ 25 ]. One can assume that compared to women who are generally confined within household works the male population is mostly involved in outdoor work activities for livelihood which makes them more likely exposed to Aedes spp.…”
Section: Discussionsupporting
confidence: 90%
“…Annual seasonal variation trends of the dengue occurrence shows, infections appear abruptly in July, just after the start of the rainy season and cases peaks in August and September, which are considered to be the months with the most favorable climate for mosquitoes breading [ 24 , 25 ]. Similar seasonal response was found in a study conducted in China and Philippines [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, DENV-2 genotype Cosmopolitan was detected in Maritime South East Asia (Indonesia, Malaysia, Singapore, and Philippines) [ 50 54 ] and South Asia (India, Bangladesh, Nepal, Pakistan, and Sri Lanka) [ 5 , 6 , 55 , 56 ]. The phylogenetic tree of the envelope genes of DENV-2 Thailand strains collected from 1964–2017 confirmed the presence of two genotypes in separate monophyletic clusters ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A. aegypti was first reported in Kathmandu in 2010 and the vectors may have now established populations up in the mountains [ 12 ]. Serotype and genotype shifts have been reported based on sequencing of specific viral regions [ 15 ]. In-depth molecular study of the virus found in the hill region of Nepal might give insights into the climatic shift of dengue disease.…”
Section: Discussionmentioning
confidence: 99%